STUDY ON THE INTEGRATION OF THE EXIGENCIES OF ACCOUNTING REGULATIONS IN THE ACCOUNTING PRACTICE OF ROMANIAN COMPANIES - Ion, Elena Iuliana; Man, Mariana (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 19 (2017): Annales Universitatis Apulensis Series Oeconomica, 2017)
This paper presents specialists’ perception regarding the importance of integrating the exigencies of the accounting regulations in the accounting practice in Romanian companies, in order to faithfully appreciate the position and financial performance of companies. The results of the research shows that a large proportion of respondents affirm that the exigencies of the accounting regulations are integrated in the accounting practice within the company in order to meet the requirements of all information users. Most of those surveyed consider that the company’s performance is closely related to satisfying the customers, employees, investors and users of financial-accounting information. The research shows that integrating the exigencies of the accounting regulations into the accounting system increases the companies’ level of responsibility The research aims to emphasise the importance of integrating the exigencies of the accounting regulations into the company’s accounting system in order to accurately assess the financial performance and increase the companies’ level of social responsibility.